Anti-inflammatory activity and identification of two ‘Sarpagan’ indole alkaloids from the leaf methanolic extract of Rauvolfia densiflora (Wall.) Benth. ex Hook. f. - Sabin, P. Q.; Girija, T. P.; Usman, A. (Current Botany, 2024)
The Apocynaceae plant group contains many bioactive compounds that are pharmacologically relevant and are used as potential medicine for many diseases. Rauvolfia densiflora Benth. ex Hook.f. (syn- Rauvolfia verticillata (Lour.) Baill.) coming under the same family known for its diverse medicinal properties. The current study was carried out to evaluate the bioactive compounds present in the extract using GC-MS analysis and to find out the anti-inflammatory potential of the extract using in-vitro methods. GC-MS analysis revealed the presence of 16 bioactive compounds with diverse pharmacological activities. Among them, Oleic Acid, 17-hydroxy-, methyl ester, trans-decahydroquinoline, and Spiro-(1,3-dioxolane-2, 3’-indolin]-2’-one possesses more important properties. Two important sarpagan indole alkaloids were also identified namely Sarpagan-16-carboxylic acid or (Z) Akuammidine and sarpagan-17-ol or Vellosiminol, which are pharmacologically important compounds with anti-inflammatory, anti-asthmatic activities. The in-vitro anti-inflammatory activity was carried out using the COX assay. COX assay showed 55.27% inhibition at a concentration of 200 μg/mL with an IC50 value of 155.38 μg/mL, this is an indication that the methanolic leaf extract R. densiflora has the potential to be developed as a non-steroidal anti-inflammatory drug (NSAID).